2022
DOI: 10.1186/s12884-021-04358-4
|View full text |Cite
|
Sign up to set email alerts
|

Facility level factors that determine consistent delivery of essential newborn care at health centers in Ethiopia

Abstract: Background Essential newborn care (ENC) is a package of interventions which should be provided for every newborn baby regardless of body size or place of delivery immediately after birth and should be continued for at least the seven days that follows. Even though Ethiopia has endorsed the implementation of ENC, as other many counties, it has been challenged. This study was conducted to measure the level of essential newborn care practice and identify health facility level attributes for consis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 25 publications
(19 reference statements)
0
5
0
Order By: Relevance
“…2021b; Fekadu et al. 2022) confirmed that drawing a partogram (a graph of labour progress and the maternal and foetal condition) could inform implementors the required steps. In contrast, three studies indicated that the lack of concrete and feasible operating procedures was a challenge (Gonfa et al.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…2021b; Fekadu et al. 2022) confirmed that drawing a partogram (a graph of labour progress and the maternal and foetal condition) could inform implementors the required steps. In contrast, three studies indicated that the lack of concrete and feasible operating procedures was a challenge (Gonfa et al.…”
Section: Resultsmentioning
confidence: 99%
“…2021b; Fekadu et al. 2022; Mwakawanga & Mselle, 2020; Nahidi, & T. S. Haidarzade M, Hajizadeh E. 2014), could improve newborn care.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations